Tactics of the 'ugly Australian' : morality, masculinity, nationalism and governance amid a cheating controversy in sport - Wade, Matthew (2021)
Cricket occupies an ambivalent place in the Australian cultural imaginary, caught between former colonial origins and current pluralist aspirations, and retaining conservative leanings that can veer into ‘ugly assimilationism’. Elite representatives are variably celebrated as national icons or uneasy sources of collective identity, given tendencies to become ‘Ugly Australians’. Within the Australian cricket team, this combustive mix of nationalism, moralism, masculinity and instrumental deviance coalesced into a win-at-all-costs ethos, culminating in brazen cheating and causing apparent diplomatic embarrassment. More significant, however, were underlying strategies of self-confessedly brutal degradation of opponents. Strategic aggression and humiliation were abetted by governing bodies that demanded success but neglected to uphold ethical standards. Moral hazards and regulatory gaps incentivized players to self-set ‘the line’ of acceptable conduct, enabling injurious tactics that included intimidation, emasculation, mockery and mass invective. A complementary argument discusses populist posturing and moral hypocrisy that were emergent during the cheating scandal, for more worthy grievances languished amid the ‘crisis in cricket’.